Complete genome sequence of deformed wing virus and black queen cell virus isolated from honeybees (Apis mellifera) in Argentina - Gonzalez, Fernanda Noemi; Ferrufino, Cecilia Gabriela; Dus Santos, Maria Jose; Carignano, Hugo Adrian (American Society for Microbiology, 2024)
We report the complete genome sequence of deformed wing virus and black queen cell virus isolated from Argentinean’s honeybees. These sequence data will be valuable for future research on the viral variants present in the country and the development of strategies to control the spread of these viruses in apiaries.